Home Gardens as Potential Roosting sites for Indian Flying Fox (Pteropus medius) in Assam, North-East India: Status and Distribution - Barman, Deepankar; Roy, Jayanta Kumar; Choudhury, Manabendra Ray; Adhikary, Pinaki; Kumar, Awadhesh; Ahmed, Tanveer; Thakur, Rupali; Nath, Anukul (Indian Forester, 2025)
The decline in available roosting sites are one of the major threats to the Indian flying fox in India. Present study investigates the status and diurnal roosting site characteristics of Indian flying fox in Assam, north-east India. A total 16,237 (colonies ranges: 45-1012) individuals of Indian flying fox were recorded from 47 roosting colonies located mostly in human dominated landscape mostly in home gardens (89%). Majority of roost (90%) had been occupied for more than ten years. Bombax ceiba (20.54%), was the most used plants for roosting followed by Bambusa tulda and Ficus rumphii. Roosting trees had an average height of 28.8 ± 0.2 m, GBH of 1.63 ± 0.49 m and canopy cover 47.7 ± 2.3%. Previous research on the status and distribution of the species within Assam was also reviewed. The present study concluded that human dominated landscape such as home gardens have significant contribution in conservation of bat species, if managed and protected properly.